6th Biennial Building Healthy Academic Communities National Summit: Abstracts from the Poster Winners - Building Healthy Academic Communities BHAC Journal (The Ohio State University Libraries, 2023)
This Spring, the National Consortium for Building Health Academic Communities, in collaboration with the University of North Carolina Wilmington, hosted the sixth Biennial National Summit - Riding the Waves of Wellbeing. Attendees participated in a variety of workshops, breakout sessions, and wellness activities. Keynote speakers included Chris and Nik Nikic, authors of 1% Better: Reaching My Full Potential and How You Can Too. Plenary presentations were provided by Abdul El-Sayed, MD, Harry A. and Margaret D. Towsley Foundation Policymaker in Residence, University of Michigan; Sheri Shaw, Assistant Dean for Student Success, University of North Carolina Wilmington; David Feldman, PhD, McCarthy Professor, Department of Psychology, Santa Clara University; and Bernadette Melnyk, PhD, APRN-CNP, FAANP, FNAP, FAAN, The Ohio State University. In addition to these outstanding activities and presentations, the Biennial National Summit also included a judged poster session. BHAC is pleased to present the abstracts from the winning posters.